2016
DOI: 10.1186/s12931-016-0407-7
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary effects of inhalation of spark-generated silver nanoparticles in Brown-Norway and Sprague–Dawley rats

Abstract: BackgroundThe increasing use of silver nanoparticles (AgNPs) in consumer products is concerning. We examined the potential toxic effects when inhaled in Brown-Norway (BN) rats with a pre-inflammatory state compared to Sprague–Dawley (SD) rats.MethodsWe determined the effect of AgNPs generated from a spark generator (mass concentration: 600–800 μg/mm3; mean diameter: 13–16 nm; total lung doses: 8 [Low] and 26–28 [High] μg) inhaled by the nasal route in both rat strains. Rats were sacrificed at day 1 and day 7 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…Whereas, ultra-structural examination of TiO2-Nps group revealed pneumocyte type II with empty lamellar bodies and microvilli on its surface. Multiple red blood cells are detected in the alveolar space; these results were in agreement with other researchers [52] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Whereas, ultra-structural examination of TiO2-Nps group revealed pneumocyte type II with empty lamellar bodies and microvilli on its surface. Multiple red blood cells are detected in the alveolar space; these results were in agreement with other researchers [52] .…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous authors [52] , thickened vessel wall with marked cellular infiltration were observed in the Ag-Nps injected lung. They proved that Ag-Nps induced pulmonary neutrophilic inflammation with the production of proinflammatory and pro-neutrophilic cytokines.…”
Section: Discussionsupporting
confidence: 93%
“…Concerning animal investigations, toxicity in the lungs, including inflammatory reactions and histopathological alterations (149)(150)(151)(152)(153)(154)(155)(156)(157)(158) were reported to be responsible for pulmonary functionality alterations (155,159) or allergic responses (160): however, other investigations have failed to detect hematological effects, systemic alterations, and pulmonary function test changes after Ag-ENM exposure (161,162). Histopathological changes in the kidney and liver (bile duct hyperplasia and necrosis) were identified after inhalation exposures, such as extra-pulmonary effects (155,158,159).…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…However, as Ag-NP can also occur as airborne dust, e.g., during nanoparticle (NP) fabrication processes, well-adapted occupational exposure levels are necessary, as well, and have been recently suggested [ 2 ]. These considerations are based on inhalation and instillation studies conducted with Ag-NP of different sizes and surface coatings [ 8 , 9 ]. These studies show that Ag-NP in the lung exhibit a high inflammatory potential and can lead to granulomatous lesions.…”
Section: Introductionmentioning
confidence: 99%